Situational and individual factors engendering willingness to speak English in foreign language classrooms - Mohammad Javad Riasati; Forough Rahimi (Cogent Education, 2018)
The present study is an attempt to investigate Iranian EFL learners’ willingness to speak English in language classrooms, and the situational and individual factors that influence their willingness to speak. The study adopts a primarily quantitative approach, followed by qualitative data aimed at expanding and elaborating on the quantitative data. One hundred and fifty six EFL learners took part in the study. A researcher-made Willingness to Speak questionnaire was used to measure willingness to speak. To shed more light on learners’ willingness to speak, semi-structured interviews were conducted with seven participants in order to arrive at richer findings. Several factors were identified as having an influence on learners’ willingness to speak, including topic of discussion, effect of interlocutor, shyness, self-confidence, teacher, and classroom atmosphere. Results can bring about pedagogical implications for language educators and curriculum developers.